Negotiating Queer Masculinities in Southeast Asian Cinema: Comparative Analysis of The Iron Ladies (2000), Arisan! (2003), Die Beautiful (2016) - Pratiwi, Cysakaren Diva; Wulan, Nur; Puryanti, Lina (IMAJI, 2025)
This article examines the construction and negotiation of queer masculinities in Southeast Asian cinema through a comparative analysis of The Iron Ladies (dir. Yongyoot Thongkongtoon, Thailand, 2000), Arisan! (dir. Nia Dinata, Indonesia, 2003), and Die Beautiful (dir. Jun Lana, Philippines, 2016). While dominant regional representations of masculinity have been shaped by heteronormative, patriarchal, and nationalist ideologies, these films offer alternative portrayals that challenge and reconfigure normative gender and sexual identities. Drawing on Edward Said’s postcolonial critique of representation and José Esteban Muñoz’s theory of disidentification, this study employs qualitative textual analysis to investigate how queer male identities are represented within specific cultural and national contexts. The findings reveal that queer masculinities in these films are articulated through strategies of disidentification, performance, and resistance, negotiating visibility and belonging without fully conforming to or rejecting dominant norms. Each film reflects the particular socio-political tensions of its national context, while simultaneously disrupting Western-centric or Orientalist constructions of queerness. Ultimately, this study demonstrates how Southeast Asian cinema functions as a critical space for reimagining queer identity and masculinity beyond colonial and heteronormative frameworks.